HIV care continuum in Rwanda: a cross-sectional analysis of the national programme. Issue 5 (May 2015) - Nsanzimana, Sabin; Kanters, Steve; Remera, Eric; Forrest, Jamie I; Binagwaho, Agnes; Condo, Jeanine; Mills, Edward J
Summary: Background: Rwanda has made remarkable progress towards HIV care programme with strong national monitoring and surveillance. Knowledge about the HIV care continuum model can help to improve outcomes in patients. We aimed to quantify engagement, mortality, and loss to follow-up of patients along the HIV care continuum in Rwanda in 2013. Methods: We collated data for individuals with HIV who participated in the national HIV care programme in Rwanda and calculated the numbers of individuals or proportions of the population at each stage and the transition probabilities between stages of the continuum. We calculated factors associated with mortality and loss to follow-up by fitting Cox proportional hazards regression models, one for the stage of care before antiretroviral therapy (ART) initiation and another for stage of care during ART. Findings: An estimated 204 899 individuals were HIV-positive in Rwanda in 2013. Among these individuals, 176 174 (86%) were in pre-ART or in ART stages and 129 405 (63%) had initiated ART by the end of 2013. 82·1% (95% CI 80·7–83·4) of patients with viral load measurements (n=3066) were virally suppressed (translating to 106 371 individuals or 52% of HIV-positive individuals). Mortality was 0·6% (304 patients) in the pre-ART stage and 1·0% (1255 patients) in the ART stage; 2247 (3·9%) patients were lost to follow-up in pre-ART stage and 2847 (2·2%) lost in ART stage. Risk factors for mortality among patients in both pre-ART and ART stages included older age, CD4 cell count at initiation, and male sex. Risk factors for loss to follow-up among patients at both pre-ART and ART stages included younger age (age 10–29 year) and male sex. Interpretation: The HIV care continuum is a multitrajectory pathway in which patients have many opportunities to leave and re-engage in care. Knowledge about the points at which individuals are most likely to leave care could improve large-scale delivery of HIV programmes. Funding: TheBill & Melinda Gates Foundation .